Textual analysis of financial statements : Disclosure quality assessment - Jančová, Kateřina; Procházka, David, 1979 říjen 10.-; Křivanec, Oto; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This paper contains the connection of textual analysis and disclosure quality assessment. By introducing frequently used textual analysis tools for extracting information content from lengthy texts, such as business reports, we facilitate the transformation of qualitative content into quantitative data. Consequently, we use this data to assess disclosure quality by implementing the fundamental and enhancing characteristics of financial reporting, as stated in the Conceptual Framework for Financial Reporting (IASB, 2010). We find that, while imprecise, textual analysis is the most efficient tool to extract information from lengthy texts and enables further use of extracted data for disclosure quality assessment. Because the fundamental and enhancing characteristics of financial reporting reflect the needs of financial report users, we conclude that their use as a proxy for disclosure quality assessment should result in a commendable image of the company’s standardized financial communications.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses